Pendidikan Perbandingan: Satu Catatan Awal Tentang Makna Ruanglingkup dan Tujuannya - Zon, Khadijah (Penerbit Universiti Sains Malaysia, 1984)
This article presents some preliminary notes on the Meaning, Scope and Purpose of Comparative Education. The different definitions of Comparative Education are traced in the context of three growth-phases of this field, namely the historical-cum-philosophical, the 'melioristic' and empiricaland-scientific phases, as have been defined by Kandel, Bereday, King, and Noah and Eckstein respec-' tively. The common denominator of all these definitions is the 'cross-cultural perspective'. Tretheway and Altbach propose also that Comparative Education look 'inwards' into the comparatists' own nation-state and attempt to help resolve some of their own national educational problems before enlarging their views to the global level. Generally one could say that Comparative Education has two main purposes - intellectual and idealistic on the one hand, and pragmatic on the other - with each of these categories incorporating other minor objectives.